2017
DOI: 10.1093/cid/cix648
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Blood Cultures in Gram-Negative Bacteremia: Are They Needed?

Abstract: FUBC added little value in the management of GNB bacteremia. Unrestrained use of blood cultures has serious implications for patients including increased healthcare costs, longer hospital stays, unnecessary consultations, and inappropriate use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 9 publications
3
61
0
3
Order By: Relevance
“…Our study revealed that FUBCs were performed in most of the patients with GNB, but less than 10% produced positive results. In contrast to gram-positive bacteremia, positive FUBC results were not common in GNB [1,3].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Our study revealed that FUBCs were performed in most of the patients with GNB, but less than 10% produced positive results. In contrast to gram-positive bacteremia, positive FUBC results were not common in GNB [1,3].…”
Section: Discussionmentioning
confidence: 69%
“…Although the positive rate of detection from follow-up blood cultures (FUBCs) in gram-negative bacteremia (GNB) is relatively low (5.8-10.9%) [1][2][3], and the risk factors for persistent GNB have not been investigated extensively, FUBCs have been routinely conducted in cases of GNB in many acute care hospitals [1][2][3][4]. Unnecessary routine blood cultures are invasive, and false positives due to contamination increase medical costs and time spent in hospitals [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, almost all previous studies included fever as a criterion. Some included microbiological persistence as a criterion for early treatment failure; however, follow-up blood cultures are not routinely recommended in GN-BSI [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…The literature for gram-negative BSI has significantly changed treatment recommendations by supporting shorter treatment durations [ 28 ], early switch to oral antibiotics [ 29 ], and demonstrating lack of benefit of repeat blood cultures [ 30 ]. Using an approach that is well described in gram-positive infections, Erickson and colleagues conducted a single-center, retrospective cohort evaluation of an antimicrobial stewardship bundle coupled with rapid diagnostic tests (RDTs) for uncomplicated gram-negative bacteremia [ 13 ].…”
Section: Resultsmentioning
confidence: 99%